The order of things: phosphate release or the power stroke, which does actomyosin do first? - Debold, Edward P.; Marang, Christopher P.; Scott, Brent D. (Frontiers in Physiology, 2025)
Myosins are a highly conserved super family of motor proteins that are responsible for driving a host of intracellular processes in eukaryotes, from muscle contraction to vesicular transport. Myosins can perform these tasks because they transduce chemical energy, from the hydrolysis of ATP into mechanical work, in the form of a power stroke. The key event in the transduction process is the putative coupling of Pi release with the power stroke; however, the timing and mechanism of coupling of these events remain unclear. Atomic structures of myosin, captured in intermediate states of its cross-bridge cycle, suggest that Pi release is required for the power stroke to occur and therefore must precede the power stroke. In contrast, most functional assays, which can measure myosin’s structural dynamics with sub-millisecond temporal and nanometer spatial resolution, suggest that the power stroke occurs less than 1 ms after forming a strong bond with actin, while Pi release occurs 10–200 ms after binding to actin, suggesting that the power stroke precedes Pi release. A host of new studies and a few new models have been put forth in recent years to attempt to reconcile these seemingly conflicting findings. Although there is not yet a consensus on the order of these events, the new information provided by these efforts is transforming our understanding of how myosin transduces energy. This knowledge has important implications for elucidating the molecular basis of a myriad of myosin-associated diseases and, therefore, for the development of compounds to treat these diseases.